Justice For All: An Overview of the Supreme Court of Missouri’s Commission on Racial and Ethnic Fairness - Hon. Lisa White Hardwick (Washington University Journal of Law and Policy, 2022)
Systematic racial and ethnic inequality can only be reversed by systematic action. After the killing of Michael Brown by the Ferguson police in August 2014, Missouri’s need for judicial and legal reform could no longer be ignored. The following year, the Supreme Court of Missouri Commission on Racial and Ethnic Fairness (“Commission”) was established to examine and review current practices and recommend measures to ensure fairness, impartiality, equal access, and participation for racial and ethnic minorities in the judicial process and in the practice of law. This Article, authored by the Commission’s Co-chair, Missouri Court of Appeals Judge Lisa Hardwick, discusses the Commission and provides an overview of its background and purpose. Judge Hardwick details some of the steps the Commission has taken towards fulfilling equitable justice in the courts, using her position as co-chair to shed light on its inner workings. Judge Hardwick shows how the Commission is well- equipped and well-positioned to meet its goals of ensuring equal access and full participation for racial and ethnic minorities in Missouri courts. The Article explains that with a successful five-year history of data collection and procedural reforms, the Commission has built a strong foundation to carry the work of racial justice into the future.
Keywords: Supreme Court of Missouri; Commission on Racial and Ethnic Fairness